2001
DOI: 10.1042/bj3560769
|View full text |Cite
|
Sign up to set email alerts
|

Amine oxidase substrates mimic several of the insulin effects on adipocyte differentiation in 3T3 F442A cells

Abstract: We have previously reported that substrates of monoamine oxidase (MAO) and semicarbazide-sensitive amine oxidase (SSAO) exert short-term insulin-like effects in rat adipocytes, such as stimulation of glucose transport. In the present work, we studied whether these substrates could also mimic long-term actions of insulin. Adipose differentiation of 3T3 F442A cells, which is highly insulin-dependent, served as a model to test the effects of sustained administration of amine oxidase substrates. Daily treatment of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
42
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 27 publications
3
42
0
Order By: Relevance
“…As to the mechanisms involved, we have demonstrated that the combination of SSAO substrates and vanadate stimulates tyrosine phosphorylation of insulin receptor substrate (IRS)-1 and -3 proteins and activates phosphatidylinositol 3-kinase (10), i.e., crucial components of insulin signal transduction. In addition, chronic incubation of 3T3 adipocytes with SSAO substrates caused an enhanced insulin sensitivity (14). In keeping with these in vitro insulinomimetic effects, chronic treatment with benzylamine and vanadate lower hyperglycemia in streptozotocin-induced diabetic rats (12).…”
mentioning
confidence: 55%
“…As to the mechanisms involved, we have demonstrated that the combination of SSAO substrates and vanadate stimulates tyrosine phosphorylation of insulin receptor substrate (IRS)-1 and -3 proteins and activates phosphatidylinositol 3-kinase (10), i.e., crucial components of insulin signal transduction. In addition, chronic incubation of 3T3 adipocytes with SSAO substrates caused an enhanced insulin sensitivity (14). In keeping with these in vitro insulinomimetic effects, chronic treatment with benzylamine and vanadate lower hyperglycemia in streptozotocin-induced diabetic rats (12).…”
mentioning
confidence: 55%
“…The exact involvement of TNF-␣ in the pathophysiology of insulin resistance in obese humans and in noninsulin-dependent diabetes mellitus is still a matter of controversy, but it is reasonable to believe that TNF-␣, in addition to other cytokines and metabolic factors, could contribute to the balance of tissular insulin sensitivity. Several recent works have reported that SSAO substrates stimulate glucose transport in rodent Marti et al, 1998;Fontana et al, 2001) or human adipocytes (Morin et al, 2001). This amine-stimulated glucose transport may thus represent an original mechanism by which circulating or locally produced amines can regulate glucose homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported that SSAO activation in response to its substrates can stimulate glucose transport in adipocytes Marti et al, 1998;Fontana et al, 2001;Morin et al, 2001). Otherwise, TNF-␣ is well known to inhibit insulin-stimulated glucose transport (Stephens and Pekala, 1991) and to be involved in the pathogenesis of obesity-associated insulin resistance (Hotamisligil, 2000;Moller, 2000).…”
Section: Tnf-␣ Modulation Of Ssao-mediated Glucose Uptake 1201mentioning
confidence: 99%
See 2 more Smart Citations